Diseño de un Sistema Contable en la Farmacia Andrey de la Ciudad de Loja, Período Enero-Junio del 2015 - Camacho Herrera, Romel Daniel (2016)
his thesis called "DESIGN OF AN ACCOUNTING SYSTEM IN THE ANDREY CITY OF LOJA PHARMACY PERIOD JANUARY-JUNE 2015", aims to provide theoretical and practical elements for the implementation of a System Multiple Account, which enable the owner to know the economic and financial situation pharmacy also complying with the provisions of the general regulations of the National University of Loja, as a requirement to qualify for the title of Engineer in Accounting and Auditing, Certified Public Accountant Auditor. To achieve the first objective: To design appropriate auxiliary records showing the actual situation of the pharmacy, in order to determine the administration and efficiency with which resources were handled during an economic period; It was met with obtaining all information relating to transactions made by the company through ancillary purchasing, sales, payment roles, social provisions, which show the real situation in which the entity is. The second objective: to develop a system of inventory control by using the system of multiple features in order to know the value and the physical existence of the goods, took him out with an inventory by physically taking products with which account the pharmacy, as are their movable and immovable property, monetary values, rights, obligations with third parties that allow you to perform operations. The third objective is: Perform all the accounting process for the financial statements in the given period, in order to know the real situation in which the identity is, it was possible to develop a plan and manual accounts according to the needs of the entity according to the movement of your transactions and documentation source Initial Inventory, State Initial 5 Situation, Daybook, Ledger, Trial Balance, Worksheet with their respective adjustments until finally determine the financial statements of the pharmacy was developed. To make the ultimate objective: Apply financial indicators to understand the economic and financial accounting process to end the situation; use indicators of liquidity, activity and indebtedness, providing guidance to the owner of the pharmacy for proper decision-making to improve it. Finally conclusions are presented, among which we highlight the correct design development of an accounting system and the application of indicators to demonstrate the economic and financial situation in which is the pharmacy and is recommended to continue applying this system, in order to improve management and business efficiency.